Pengalaman, Fasilitas Kantor, dan Lindgkungan Kantor Mempengaruhi Produktivitas dan Kinerja Karyawan Bappeda Kabupaten Muara Enim - Walizi, Hevan; Basyith, Abdul; Yulanda, Delvina (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
This study aims to analyze the influence of Experience, Office Facilities, and the office environment on the productivity and performance of employees at the Regional Development Planning Agency of Muara Enim Regency. The number of samples used is the census method, so the sample size is all employees of the Muara Enim Regency Bappeda, totaling 72 respondents. The independent variables are Experience (X1), Office Facilities (X2), and Work Environment (X3), while the dependent variables are Productivity (Y1) and Office Performance (Y2). The analysis technique is OLS Regression. The results of the study show that the variables Experience, office facilities and the environment have a significant positive effect on the productivity and performance of employees of the Regional Development Planning Agency of Muara Enim Regency